Review of Inside Story: How Narratives Drive Mass Harm. Lois Presser - McLaughlin, Olivia Marie (2019)
Lois Presser, Inside Story: How Narratives Drive Mass Harm. University of California Press (2018), 200 pages, $85 (hardcover), $29.95 (paperback)